Impelementasi Disiplin Kerja Dan Produktivitas Kerja Perspektif Ekonomi Islam - Rija Aini; Sri Sudiarti (Pusat Riset Manajemen Dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia, 2022)
This study aims to analyze and determine the implementation or application of work discipline and work productivity in the Regional Office of the Ministry of Religion of North Sumatra Province. This study uses a descriptive approach with qualitative methods that use interviews, observation, and documentation as a technique to obtain research data. The subjects in this study were employees who worked in the office of the Ministry of Religion of North Sumatra Province. The results of the study explain that the implementation of work discipline which includes indicators of attendance, compliance with work regulations and standards, as well as a high level of vigilance and then work productivity variables with indicators of ability, results achieved, morale, self-development, quality and efficiency have been implemented entirely. by employees with a good level of assessment to quite good in its implementation in the field. Islamic economics in interpreting work is not just to meet the needs of life but as a form of existence, and self-servitude as a human to Allah Swt